Analysis of Vibration Reduction by Damping Using Simple Analytical Modelling - Goran Pavić (Shock and Vibration)
The performance of different solutions to global vibration reduction using external damping is discussed. The solutions are either uneven distribution of structural damping or use of vibration absorbers. To this end, a comparative study is carried out, built on simple analytical models. It is shown that a well-chosen solution can produce a substantial reduction of global vibration level. It is further shown that the overall damping effect critically depends on the mutual interaction between the applied damping device and the damped structure. Qualitative guidelines are provided about the selection of appropriate parameters that affect damping performance.